Impact of drugs on intradialytic hypotension: Antihypertensives and vasoconstrictors. Issue 6 (5th July 2017) - Chang, Tara I.
Abstract: Intradialytic hypotension (IDH) is a common complication of hemodialysis and is associated with numerous adverse outcomes including cardiovascular events, inadequate dialysis, loss of vascular access, and death. It is estimated that approximately 20%‐30% of all dialysis sessions are affected by IDH. In seeking ways to reduce the occurrence of IDH, dialysis providers often turn to pharmacological approaches: withholding antihypertensive medications prior to hemodialysis or administering vasoconstrictor medications. This review will focus on what is known about the relation between antihypertensive medications and IDH, and summarize studies that have examined the efficacy of vasoconstrictor medications on IDH, including midodrine, arginine vasopressin, and droxidopa. However, there is currently scant evidence that any pharmacological approach is particularly effective in reducing IDH. Additional studies of potential treatments for IDH are needed, and should examine not only hemodynamic effects such as changes in nadir blood pressure during dialysis, but also on patient‐centered and clinical outcomes such as symptoms of IDH, quality of life, and cardiovascular events.